Connecting Data for Consumer Preferences, Food Quality and Breeding in support of Market-oriented Breeding of Root, Tuber, and Banana Crops - Arnaud, E.; Menda, N.; Tran, T.; Asiimwe, A.; Kanaabi, M.; Meghar, K.; Forsythe, L.; Kawuki, R.S.; Ellebrock, B.; Siraj Kayondo, I.; Agbona, A.; Zhang, X.; et al. (Wiley, 2024)
The 5-year project ‘Breeding Roots, Tubers and Banana products for end user preferences’ (RTBfoods) focused on collecting consumers’ preferences on twelve food products to guide breeding programs. It involved multidisciplinary teams from Africa, Latin America, and Europe. Diverse data types were generated on preferred qualities of users (farmers, family and entrepreneurial processors, traders or retailers, and consumers). Country-based Target Product Profiles (TPP) were produced with a comprehensive market analysis, disaggregating gender's role and preferences, providing prioritised lists of traits for the development of new plant varieties. We describe the approach taken to create, in the RTB breeding databases, a centralised and meaningful open access to sensory information on food products and genotypes. Biochemical, instrumental textural, and sensory analysis data are then directly connected to the specific plant record while user survey data, bearing personal information, were analysed, anonymized, and uploaded in a repository. Names and descriptions of food quality traits were added into the Crop Ontology, along with the various methods of measurement used by the project, for labelling data in the databases. The development and application of Standard Operating Procedures, data templates and adapted trait ontologies improved the data quality and its format, enabling to link it to the studied plant material when uploaded in the breeding databases or in repositories. Some modifications to the database model were necessary to accommodate the food sensory traits and sensory panel trials.